Urban rainwater utilization: A review of management modes and harvesting systems - Xu, Jiayi; Dai, Jiangyu; Wu, Xiufeng; Wu, Shiqiang; Zhang, Yu; Wang, Fangfang; Gao, Ang; Tan, Yanping (Frontiers in Environmental Science, 2023)
Due to the impact of climate change and rapid urbanization, the global urban flood control and water environment security issues are particularly prominent. As an effective means to solve urban flood control and water environment security issues, urban rainwater resource utilization has become a global research and application hotspot. This paper briefly combed the development history of rainwater utilization management modes in advanced countries, classified urban rainwater utilization measures from the utilization stage, which are divided into three forms: source control, medium transmission and terminal treatment, summarized the advantages, disadvantages and scope of application of these measures, quantitatively analyzed the rainwater pollution control and flood control utilization effects of these measures, and prospected their application prospects, which is expected to provide reference for pollution control of relevant measures in urban rainwater measures’ construction.